Balancing Free Speech and National Security: Analyzing the Legal and Social Implications of Sedition Laws in India (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This paper examines the complex interplay between free speech and national security in India, with a focus on the legal and social implications of sedition laws. Rooted in colonial-era legislation, India’s sedition law Section 124A of the Indian Penal Code has sparked intense debate on its relevance and application in a modern democratic society. While the law aims to curb activities that threaten the unity and sovereignty of the nation, critics argue that it infringes on constitutional rights, stifling political dissent and freedom of expression. This study explores the historical evolution and intended purpose of sedition laws, analyzing landmark judicial interpretations and key cases that have shaped their use. Through a multidisciplinary approach, the paper assesses the socio-political impact of sedition prosecutions on civil liberties, the media, and democratic discourse. Furthermore, it evaluates the tension between safeguarding national security and upholding individual freedoms, drawing on comparative perspectives to explore alternative approaches to handling dissent. In conclusion, the paper provides recommendations for policy reforms that balance security concerns with the constitutional mandate for free expression, advocating for a legal framework that respects democratic values while addressing legitimate security threats.